Recent Advances in Cannabinoid Research 2019
DOI: 10.5772/intechopen.79321
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a High-Throughput In Vivo Model for Testing the Bioactivity of Cannabinoids

Abstract: Zebrafish represent an established vertebrate model system that helps to bridge the research gap between cell line/invertebrate studies and mammalian systems. While the initial testing of tetrahydrocannabinol (THC) using Zebrafish occurred in 1975, zebrafish are currently a burgeoning model for testing the bioactivity of cannabinoids. Zebrafish express both CB1 and CB2 receptors along with all of the other major endocannabinoidrelated genes. Zebrafish endocannabinoid gene function has been associated with addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 127 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have shown that zebrafish have a highly homologous endocannabinoid system to that of humans and that behavioral models can be used to assess the bioactivity of the endocannabinoid system along with its potential as a therapeutic target (Krug & Clark, 2015 ; Ellis, 2018 ; Oltrabella et al, 2017 ). The previous studies have primarily tested pure compounds or mixtures thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that zebrafish have a highly homologous endocannabinoid system to that of humans and that behavioral models can be used to assess the bioactivity of the endocannabinoid system along with its potential as a therapeutic target (Krug & Clark, 2015 ; Ellis, 2018 ; Oltrabella et al, 2017 ). The previous studies have primarily tested pure compounds or mixtures thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules 2022, 27, x FOR PEER REVIEW 2 of 23 experiments in pre-clinical testing and increase the rate of success in such models, many alternative models are being developed [1][2][3]. Zebrafish (Danio rerio; ZF) has become an important pre-clinical in vivo vertebrate model, which is widely applied in drug discovery to study the pharmacology of new drug candidates [5][6][7][8][9][10]. Eight small molecules which were initially discovered in ZF models have proceeded into clinical trials during the past decade [1,[11][12][13][14][15][16][17][18], demonstrating that the use of ZF models can contribute to successful translation [1,18].…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish is an important model organism that is widely used in pharmacogenetics, neuropharmacology, and environmental studies [ 20 ]. Recently, it has been used as a model organism in the study of cannabinoids [ 21 ] because it expresses both CB1 and CB2 receptors and all the other major endocannabinoid-related genes, even at very early-life stages [ 16 ]. The endocannabinoid gene function of zebrafish has been associated with addiction, anxiety, development, energy homeostasis and food intake, immune system function, learning, and memory [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been used as a model organism in the study of cannabinoids [ 21 ] because it expresses both CB1 and CB2 receptors and all the other major endocannabinoid-related genes, even at very early-life stages [ 16 ]. The endocannabinoid gene function of zebrafish has been associated with addiction, anxiety, development, energy homeostasis and food intake, immune system function, learning, and memory [ 21 ]. Since zebrafish embryos reside in an aqueous environment, almost any water-soluble chemical can easily be administered to developing embryos to monitor their effects on development.…”
Section: Introductionmentioning
confidence: 99%